Epidemiological obfuscation
1 online resource (312 pages)
Keywords: Epidemiology ostensibly exists to reveal and ascribe features to burdens of disease at a population level. However, as the designated arbiter of visibility in public health, it is well-positioned to also obscure burdens of disease with significant implications for both social justice and disease control. This edited volume brings together empirical accounts of epidemiological obfuscation developed by public health researchers from diverse fields, including medicine, history, anthropology, sociology, epidemiology, and rhetoric. In reading across these rich accounts, we begin to characterise what epidemiological obfuscation is, the situations in which it occurs, and the practices underlying it. As such, the book serves not only as a catalogue of independently interesting and robustly developed accounts of important episodes in the history and contemporary practice of epidemiology but also as a foundational body of scholarship on this central but oft overlooked aspect of epidemiology, namely, its ability to obscure as well as elucidate.